Analysis of Dynamic Tension in Belt During Transient Condition of Belt Conveyor System by Lagrange’s Approach - Sakharwade, Sanjay G; Nagpal, Shubharata (International Journal of Computer Sciences and Engineering, 2019)
In belt conveyor system, belt is the key component contributing 25% to 50% of total cost of the system. This paper presents a simulation study of dynamic tension in the belt. Conveyor belt is a traction component which transmits power and motion, and also carrying material load. Tension developed in the belt directly governs design and strength of structural support system, pulley assembly and the drive. Traditionally, belt tension is studied by static analysis and large factor of safety (8-10) considered for design. Conveyor belt consist of fabric carcass with a protective rubber cover, thus can be represented by a viscoeleastic model. Belt conveyor system is simplified into series of lump mass parameter and dynamic characteristic of the belt studied using Lagrange’s approach. Simulation results indicates that during full load starting condition, dynamic tension suddenly rise 1.82 times more than steady state running tension value in the belt. Dynamic analysis data useful for safe and reliable running, lowering factor of safety, improve stability and reduced belt stresses during starting.